Pengaruh Kemampuan Berbahasa Anak Melalui Perpustakaan Bersinar TK Aba Takerharjo: Pengaruh Kemampuan Berbahasa Anak Melalui Perpustakaan Bersinar TK Aba Takerharjo - Mar’atush Sholihah; Daroe Iswatiningsih (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
This study aims to analyze the impact of the "Perpustakaan Bersinar" program on early childhood language development at TK ABA Takerharjo. The program is designed to create a fun and child-friendly library environment, combining interactive activities with local culture. A qualitative descriptive approach was used, with data collected through observation, interviews, and documentation. The results show that the program successfully improved children's reading interest and language skills, as evidenced by the increased number of library visits and children's more expressive and creative language abilities. The success of the program was also supported by the active involvement of parents and teachers in creating a supportive literacy ecosystem. This program significantly contributes to early childhood literacy development